Definition of factor Xa inhibitor–related, life‐threatening gastrointestinal bleeding and guidance on when to use reversal therapy: A Delphi panel - Gregory J. Fermann; Brooks D. Cash; Nayantara Coelho‐Prabhu; Marc Maegele; Roland Bingisser; Vinay Sehgal; Alexander T. Cohen; Anna Hundt Golden; Jon Russo; Mark Price; Allen Mangel; Bruce Koch; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Objective To define and contextualize life‐threatening gastrointestinal (GI) bleeding in the setting of factor Xa (FXa) inhibitor therapy and to derive a consensus‐based, clinically oriented approach to the administration of FXa inhibitor reversal therapy. Methods We convened an expert panel of clinicians representing specialties in emergency medicine, gastroenterology, vascular medicine, and trauma surgery. Consensus was reached among the clinician panelists using the Delphi technique, which consisted of 2 survey questionnaires followed by virtual, real‐time consensus‐building exercises. Results Hypovolemia and hemodynamic instability were considered the most important clinical signs of FXa inhibitor–related, life‐threatening GI bleeds. Clinician panelists agreed that potentially life‐threatening GI bleeding should be determined on the basis of hemodynamic instability, signs of shock, individual patient characteristics, and clinical judgment. Last, the panel agreed that all patients with life‐threatening, FXa inhibitor–associated GI bleeding should be considered for FXa inhibitor reversal therapy; the decision to reverse FXa inhibition should be individualized, weighing the risks and benefits of reversal; and when reversal is elected, therapy should be administered within 1 h after initial emergency department evaluation, when possible. Conclusions Consensus‐based definitions of life‐threatening GI bleeding and approaches to FXa inhibitor reversal centered on hemodynamic instability, signs of shock, individual patient characteristics, and clinical judgment. The results from this Delphi panel may inform clinical decision‐making for the treatment of patients experiencing GI bleeding associated with FXa inhibitor use in the emergency department setting.